Classification of the Regular Components of Two-Dimensional Inner Maps - Vlasenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We propose a topological classification of dynamical systems generated by two-dimensional inner maps on the fully invariant regular components of a wandering set with special attracting boundary (to within the topological conjugacy).